Our journey through high functioning autism and asperger syndrome : a roadmap - Andron, Linda, 1946- (Jessica Kingsley, 2001)
This is an excellent travelers' guide because it is written by people who have been there. The stories are enthralling and the authors' experiences enable us to understand the culture and perspective of people with autistic spectrum disorder. This book is recommended for anyone who has embarked on a journey to explore a part of our world that we have only recently discovered.' - from the foreword by Tony Attwood 'I had a great many of my hunches and hopes confirmed when I read the words of the generous parents, and their even more generous children, who contributed to this book ... Most important, I learned it is possible to be inspired to see the glass as half full, no matter how many leaks there seem to be in the cup ... I believe the community who reads this book will join me in thanking those who wrote it, for their courage, their wit and their plethora of ideas.' - from the foreword by Liane Holliday Willey For the families who have contributed to this book, living with autism spectrum disorders has been a journey of self-discovery. With honesty and humor, they describe the ways autism has affected their daily lives, the challenges they have faced and the approaches they have found beneficial. They share their practical and original strategies for dealing with issues such as helping children to develop empathy and humor, developing and maintaining friendships and explaining their autism spectrum disorders to other people. This book will be a source of advice and inspiration for families of children with autism and the professionals who work with them. It is practical, realistic and positive - autism is seen as something to be understood and celebrated. As 11-year-old Glen states in the Appendix, written by some of the children with autism featured in the book: 'I like myself and consider my difference something positive.' Linda Andron is a licensed clinical social worker, Adjunct Lecturer in Psychiatry and Bio-Behavioural Sciences and Clinical Instructor at the University of California at Los Angeles. She is the director of the UCLA Family Support Community Program and the clinical director of the Center for Asperger's Assessment and Intervention at the HELP Group. She has worked with over 500 families of children with High Functioning Autism and Asperger Syndrome and is a member of the Professional Advisory Board of the Autism Society of Los Angeles. She has written many articles and chapters on developmental disabilities.